Efficient partnership dissolution under buy/sell clauses - Maria Angeles de Frutos; Thomas Kittsteiner (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
When a partnership comes to an end partners have to determine the terms of the dissolution. A well known way to do so is by enforcing a buy/sell option. Under its rules one partner has to offer a price for the partnership and the other agent can choose whether she wants to sell her share or buy her partner's share at this price. It is well known that in a model with private valuations this dissolution rule may generate inefficient allocations. However, we here show that if partners negotiate for the advantage of being chooser, then this buy/ sell provision results in an ex-post efficient outcome. This result helps to explain why such provisions are so widely introduced in partnership contracts.
Keywords: C72; D44; 330; Partnerschaftsgesellschaft; Betriebsübergang; Übernahme; Nichtkooperatives Spiel; Auktionstheorie; Theorie